“Partial Annular Pancreas Causing Obstruction of the First Part of the Duodenum: An Exceedingly Rare Conundrum—A Rare Case Report and Comprehensive Literature Review” - Saurav Jha; Sabin Luitel; Niraj Kushwaha; Sweta Singh; Sulav Kumar Jha (Clinical Case Reports)
ABSTRACT The annular pancreas is one of the very few congenital anomalies associated with gastric outlet obstruction. Usually, it is associated with obstruction of the second part of the duodenum, but to the authors' knowledge, this is the first reported case of the partial annular pancreas obstructing the first part of the duodenum, leading to late presentation of gastric outlet obstruction. As clinicians, we should be vigilant about the causes of abdominal fullness and pain and consider the annular pancreas an important differential diagnosis. It also challenges our predetermined concept of obstruction of the second part of the duodenum secondary to the annular pancreas. Even though the annular pancreas rarely obstructs the first part of the duodenum, it should always be kept in the back of our mind while diagnosing and managing elderly patients presenting with features of gastric outlet obstruction. This paper highlights the atypical presentation of the annular pancreas and how appropriate radiological investigation can clinch the uncommon diagnosis and help in the appropriate management.